RELIGION AND CONTEMPORARY ART a curious accord. - Bernier, Ronald R.; Smith, Rachel Hostetter ([S.l.] : ROUTLEDGE, 2023)
Religion and Contemporary Art sets the theoretical frameworks and interpretive strategies for exploring the re-emergence of religion in the making, exhibiting, and discussion of contemporary art. Featuring essays from both established and emerging scholars, critics, and artists, the book reflects on what might be termed an "accord" between contemporary art and religion. It explores the common strategies contemporary artists employ in the interface between religion and contemporary art practice. It also includes case studies to provide more in-depth treatments of specific artists grappling with themes such as ritual, abstraction, mythology, the body, popular culture, science, liturgy, and social justice, among other themes. It is a must-read resource for working artists, critics, and scholars in this field, and an invitation to new voices "curious" about its promises and possibilities.
Keywords: ART / Criticism; ART / History / Contemporary (1945-); RELIGION / General; Christianity and art; Christianity and the arts; Art, Modern -- 21st century